A great enhancement of both strength and plasticity in a dual-phase high-entropy alloy by multi-effects of high carbon addition. (January 2023) - Hu, Conghui; Zhang, Jianlei; Zhang, Yunhu; Song, Changjiang; Zhai, Qijie
Graphical abstract: Highlights: A great enhancement of both strength and plasticity in a dual-phase Al10 (FeNiCoMn)90 HEA was achieved by multi-effects of high carbon addition. Carbon addition in the Al10 (FeNiCoMn)90 HEA can increase the fraction of fcc phase, change the distribution of bcc phase and promote the transition from wavy slip to planar slip. Carbides precipitation was not observed in the Al10 (FeNiCoMn)90 HEA when carbon content was as high as 3 at.%. As a result, its strength and plasticity increases simultaneously due to phase modulation and interstitial strengthening. When carbon content reached to 4 at.%, the nano-scale carbides precipitation in the Al10 (FeNiCoMn)90 C4 HEA stimulated and improved the strength further by precipitation strengthening. Abstract: High-entropy alloys (HEAs) have become an interesting research area for the novel alloying design paradigm. Interstitial carbon has usually been introduced to enhance mechanical properties of HEAs. To achieve addition of high carbon, this work designed a dual-phase Al10 (FeNiCoMn)90 HEA without strong carbide-forming elements. The results showed that adding 3 at.% carbon did not cause the precipitation of carbides in this HEA, and its yield strength and plasticity increased by 237 MPa and 26.2 %, respectively, which was due to the increase of fcc phase fraction, the distribution change of bcc phase and interstitial strengthening. Addition of 4 at.% carbon only caused the precipitation of nano-scale carbides in the matrix and the yield strength and plasticity increased by 455 MPa and 5.5 %, respectively, resulted from phase modulation, interstitial strengthening and precipitation strengthening. Simultaneously, the transition from wavy slip to planar slip and the formation of microbands after carbon addition, which also led to an increase of plasticity. This work provides a promising method that if coarse carbides can be avoided, high carbon addition enhances both strength and plasticity in a dual-phase HEA by multi-effects including phase modulation, interstitial strengthening, precipitation strengthening and deformation mechanism transition.